Circular Economy as a Management Model in the Paradigm of Sustainable Development = Gospodarka cyrkularna jako model zarządzania w paradygmacie zrównoważonego rozwoju - Skawińska, Eulalia; Zalewski, Romuald I. (Zielona Góra: Faculty of Economics and Management Press)
The following paper explores circular economy as a model of management within the framework of sustainable development. Its structure comprises 4 parts. The first part illustrates the role of sustainable development as an emerging paradigm in the theory of modern economics and in the recent policy of the European Union. In the second part, the authors demonstrate the applicability of sustainable development based on the relevant management models on the micro, meso and macro levels of economy.
Keywords: rozwój zrównoważony; modele; gospodarka cyrkularna; sustainable development; management models; circular economy